Evaluation of markers out of the steroid profile for the screening of testosterone misuse. Part II: Intramuscular administration. Issue 5 (28th December 2017) - Kotronoulas, Aristotelis; Gomez‐Gómez, Àlex; Fabregat, Andreu; Segura, Jordi; Yang, Sheng; Xing, Yanyi; Moutian, Wu; Marcos, Josep; Joglar, Jesús; Ventura, Rosa; Pozo, Oscar J.
Abstract: In the fight against doping, the introduction of alternative markers to the steroid profile can be considered as an effective approach to improve the screening capabilities for the detection of testosterone (T) misuse. The aim of this study was to evaluate the potential of several T metabolites (cysteinyl conjugated and glucuronoconjugated resistant to enzymatic hydrolysis) to detect both the transdermal and the intramuscular administration of T. In Part I of the study, we studied the potential of these metabolites for the detection of T transdermal administration. Results revealed that resistant glucuronides can be a suitable complement to the current steroid profile. In this, Part II, dedicated to the intramuscular administration, we studied the potential of cysteinyl conjugated, resistant glucuronoconjugated and 1‐cyclopentenoylglycine (1‐CPG) for the detection of a single intramuscular injection of T cypionate. Possible differences in the excretion profile of all markers were explored between individuals with low basal (n=6) and medium basal (n=6) values of the testosterone/epitestosterone ratio (T/E). The results showed that all tested markers presented low intra‐individual stability in basal conditions. Despite this, all glucuronoconjugated markers and 1‐CPG, but not the cysteinyl conjugated markers, provided detection windows that were similar or longer than those obtained by markers currently included in the steroid profile. Based on the results obtained from the 2 parts of this study and from previously reported data, the potential applicability and the limitations of including these markers in the steroid profile are discussed. Abstract : The use of alternative markers can improve the screening capabilities for the detection of testosterone misuse. In Part II of this study, we studied the potential of cysteinyl conjugated, resistant glucuronoconjugated and 1‐cyclopentenoylglycine (1‐CPG) for the detection of a single intramuscular injection of T cypionate. Glucuronoconjugated markers and 1‐CPG, but not cysteinyl conjugated markers, provided detection windows that were similar or longer than those obtained by markers currently included in the steroid profile.